(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2022)
The covid-19 pandemic generated new study modalities, including virtual classes, that is, synchronous subjects, live classes with the teacher and asynchronous activities commissioned by the teacher that were fundamental for the times we were going through in society. The objective of this article is to know the impact of virtual education on the academic performance of students of the Natural Resources and Environment Economics chair. The methodology of the study is crosssectional - quantitative since the data was collected in a certain period online. The main results were that virtual classes are more viable when students handle technologies in an ideal way, followed by learning platforms and video conferencing tools. Finally, future research focuses on including new forms of virtual learning that are two-way between students - teachers, which are set in society for the benefit of current and future generations.